1996
DOI: 10.1128/jcm.34.2.413-416.1996
|View full text |Cite
|
Sign up to set email alerts
|

Genome analysis of adenovirus type 3 isolated in Japan

Abstract: Adenovirus type 3 (Ad3) isolates, isolated from 45 patients with acute conjunctivitis during the year 1990 in Japan, were studied by DNA restriction enzyme analysis with restriction endonucleases recognizing 6-bp sequences (BamHI, SmaI, HindIII, BglII) and endonucleases recognizing 5-or 4-bp sequences (HinfI and TaqI). All 45 isolates of Ad3 were identified as the genome type Ad3f by six endonucleases. They were further classified into three varieties by HinfI, varieties H 1 (87.5%), H 2 (8.9%), and H 3 (2.2%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 16 publications
0
8
1
Order By: Relevance
“…However, four new variants were observed in 1992. In 1990, a nationwide epidemiological surveillance of infectious conjunctivitis in Japan detected only one genotype, Ad3f, in 45 isolates of Ad3 [Shiao et al, 1996]. In contrast to the finding of only one genotype of Ad3, Ad3f, in 1990, it is notable that we have identified the emergence of four new genotypes in 8 of 55 Ad3 isolates in this study, from patients with acute conjunctivitis only 2 years after the former investigation.…”
Section: Discussioncontrasting
confidence: 62%
See 4 more Smart Citations
“…However, four new variants were observed in 1992. In 1990, a nationwide epidemiological surveillance of infectious conjunctivitis in Japan detected only one genotype, Ad3f, in 45 isolates of Ad3 [Shiao et al, 1996]. In contrast to the finding of only one genotype of Ad3, Ad3f, in 1990, it is notable that we have identified the emergence of four new genotypes in 8 of 55 Ad3 isolates in this study, from patients with acute conjunctivitis only 2 years after the former investigation.…”
Section: Discussioncontrasting
confidence: 62%
“…Li et al [1996] found that Ad3a2 was predominant in children with pneumonia over a 27year period in China, except in 1984 when Ad3a4 was the most prevalent genotype. In contrast, Guo et al [1988] and Shiao et al [1996] identified solely Ad3f in patients with conjunctivitis in 1986and 1990, respectively. Itakura et al [1990 also reported that Ad3f predominated (84%) in conjunctivitis in 1986 in Japan.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations